Central Asian art - Lukonin, V. G. (Vladimir Grigorʹevich) (Parkstone Press International, 2013)
The strict prohibition on the representation of the humanform has channeled artistic creation into architecture andarchitectural decoration. This book is a magical tourthrough Central Asia - Khirgizia, Tadjikistan, Turkmenia, and Uzbekistan - a cradle of Ancient civilisations and arepository of the Oriental arts inspired by Buddhism andIslam. There are magnificent, full-colour photographs of theabandoned cities of Mervand Urgench, Khiva, the capital ofthe Kharezm, with its mausoleum of Sheikh Seid Allahuddin, and, the Golden Road to Samarkand, the Blue City, acenter of civilisation for 2,500 yea.